The Study for Calling and Academic Major Satisfaction of the Nursing Students - Park, Sun-Young (International Journal of Psychosocial Rehabilitation, 2020)
Background/Objectives: The purpose of this study was to examine the relationship between the vocation of the nursing profession and the satisfaction in their major of university students in nursing departmentsMethods/Statistical analysis: Data were collected by directly recording responses to a questionnaire from 116 senior students in the College of Nursing. Collected data were statistically processed using the SPSS statistics 21 program. The degree of vocation and satisfaction in major according to general characteristics measured by t-test and one way ANOVA, and person correlation was used for the relationship between the degree of vocation and degree of satisfaction in majors.Findings: The average degree of vocation of the subjects was 32.53 ± 7.37 points. The vocation was examined in three sub-domains - transcendental calling, purpose/meaning, and prosocial orientation with scores of 9.76± 3.46 points for transcendental calling, 11.59 ± 2.74 points for purpose/meaning, and 11.18 ± 2.40 points for prosocial orientation. There was a statistically significant difference in the vocation of subjects according to religion (t = 9.521, p = 0.000) and grades (t == 4.584, p = 0.002). The subjects' degree of satisfaction in major showed an average of 22.8 ± 4.69 points. The subjects’ satisfaction in their major showed statistically significant differences according to selection of academic department (t == 4.901, p = 0.009) and grades (t== 3.802, p = 0.006). There was a strong correlation between subjects’ calling and their Academic Major Satisfaction (r = 0.455, p = 0.000).Improvements/Applications: Based on the results of this study, we propose a study on the development of a nursing vocational education curriculum